Kościół Surb Sargis w Tekor w Armenii. Między Persją a Bizancjum - Próchniak, Daniel (Vox Patrum, 2016)
The Surb Sargis (St. Sergei’s) church in Tekor, in the Shirak region of the present-day Turkey, is nowadays in total ruin. Fortunately, before its destruction by the 1911 earthquake, it had been extensively studied (e.g. by T. Toramanian and J. Strzygowski) and the documentation preserved allows us to treat it as one of the most important early-Christian buildings in both Armenia and the whole Orbis Christianus (Fig. 1-3). It is highly probable that the church was built at the site of an earlier pagan temple, utilising the former building’s tall 9-step crepidoma. Between the beginning of the 4th and the ending of the 5th century a three-nave basilica without a dome was built on the earlier base, only to be thoroughly rebuilt in the years 478-504 (dating based on the inscription at the lintel of the western portal; Fig. 4). After the rebuilding, the church acquired its 9-square structure designed by 3 naves and 3 bays. The central bay was covered with a small cupola, or rather, a cupola-structure (Fig. 5 and 7). Taking into account the contemporary state of research one may suppose that this innovative construction is the earliest known link in the process of emerging of the cross-cupola plan of churches, dominating till today in the church architecture of Eastern Christianity. The reduction of the corners of the central bay – in order to adjust its square shape to the circular base of the dome – was achieved by the construction of four small squinches (Fig. 8). This solution was most probably taken over from the 2nd – 3rd-century architecture of Persia, with which the pre-Christian Armenia had long maintained strong and varied contacts. Apart from the Tekor basilica, squinches were also used in two other buildings on the Ararat Upland near Erevan: in the small grave chapel at the Voghjaberd cemetery (5th – 6th century; Fig. 9-12) and in the one-nave church Surb Poghos- Petros (St. Paul and Peter’s) in Zovuni (between the ending of the 5th and the turning of the 6th and 7th centuries). These examples allow one to treat Armenia as a bridge between the architecture of Persia and Byzantium, where similar constructions appeared and spread widely in later periods.